A Review of Theoretical Approach to Sweetness in Chemical Compounds - Yuniarta, Tegar Achsendo; Putra, Purnawan Pontana (Fakultas Farmasi, Universitas Surabaya, 2024)
The relationship between humans and the sweet sensation is a challenge in itself. The concept of taste undergoes dynamic transformations throughout human civilization, reflecting individuals evolving preferences and experiences. Taste, as an experiential phenomenon, intricately involves the physiological aspects of the human body, with a direct correlation to signal transmission within the brain. The primary objective of this study is to unravel the chemical characteristics that contribute to the generation of sweet flavours. The research investigates the complex interplay between chemical structures and taste perception by utilizing a comprehensive review of literature from diverse sources, including books and scholarly articles from various publishers. Various analytical techniques, such as ligand-based glucophore modeling, quantitative structure-activity relationships, and the prediction and discovery of sweet receptors, are employed to understand the effects of chemical structures on sweetness. By exploring how the chemical composition of substances influences taste, this research aims to provide valuable insights into the molecular foundations of flavour, advancing our understanding of the complexities that underlie the human gustatory experience. Submitted: 27-08-2024, Revised: 29-10-2024, Accepted: 24-12-2024, Published regularly: December 2024